2015
DOI: 10.3201/eid2108.141995
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis E Virus Infection in Pigs at the Time of Slaughter, United Kingdom, 2013

Abstract: Pigs raised in the United Kingdom are unlikely to be the source of UK human infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 28 publications
(34 reference statements)
3
89
2
Order By: Relevance
“…Based on the tendencies found in our study (HEV IgG prevalence, serological evidence of (post)acute HEV infection) and the support from literature [38], we hypothesize that professional exposure to domestic pigs is a stronger risk factor than having occasional contact to wild boar when hunting. This can be explained by the remarkably high circulation of HEV in domestic pigs [54,[61][62][63][64].…”
Section: Discussionmentioning
confidence: 94%
“…Based on the tendencies found in our study (HEV IgG prevalence, serological evidence of (post)acute HEV infection) and the support from literature [38], we hypothesize that professional exposure to domestic pigs is a stronger risk factor than having occasional contact to wild boar when hunting. This can be explained by the remarkably high circulation of HEV in domestic pigs [54,[61][62][63][64].…”
Section: Discussionmentioning
confidence: 94%
“…HEV-3 and HEV-4 RNA is present throughout the pork food chain worldwide [130,133,139,140,141,142,143]. Studies have reported that 3%–11% of pig liver samples at the slaughterhouse are HEV positive in France (4%) [144], the Netherlands (6.5%) [145], Czech Republic (5%) [141], Italy (6%) [140], Spain (3%) [140], the United Kingdom (3%) [146], Japan (5%) [147] and the US (11%) [148].…”
Section: Transmission Pathways Of Zoonotic Hevmentioning
confidence: 99%
“…In Europe, high HEV seroprevalence has been detected in swine from Spain [143, 144], Italy [145147], Norway [29], Denmark [148], UK [149, 150], Estonia [151], Germany [152, 153], or Switzerland [154, 155]. According to the seroprevalence data, 76% to 98% of Spanish swine farms have evidence of HEV presence [143, 144, 156, 157].…”
Section: Hev In Animalsmentioning
confidence: 99%